Breastfeeding Policies of Otolaryngology Residency Programs - Reese, Alyssa; DiNardo, Lauren; Powers, Kristina; Favre, Nicole; Sullivan, Meagan; Carr, Michele (International Journal of Medical Students, 2024)
Background: Women entering surgical residencies must determine which programs best fit their career and family goals. The purpose of this study was to determine if breastfeeding policies are available on otolaryngology residency program websites. Methods: A total of 122 publicly available otolaryngology residency program websites were reviewed for the presence of a breastfeeding policy and lactation information. The percentage of residents and faculty that are women in each program as well as the program’s region, size, and affiliation with a top 50 hospital for ear, nose, and throat care were determined. Frequencies and nonparametric analyses were calculated when appropriate. Results: None of the otolaryngology residency programs had a breastfeeding policy posted directly on their website. A link to a Graduate Medical Education (GME) website that contained a breastfeeding policy was present on 20 (16.4%) program websites, and 31 websites (25.4%) had information about lactation facilities on the GME website or another page that could be found through the search bar; 17 (23.0%) of the large residency programs contained the link to the GME website, whereas only 3 (6.25%) of the small programs did (p = 0.015). Residency programs that were affiliated with a top 50 hospital for ear, nose, and throat care were more likely to have a link to the GME website with a breastfeeding policy than those not affiliated (13 [29.5%] vs. 7 [8.9%], respectively; p = 0.003). Conclusion: Otolaryngology residency programs do not provide breastfeeding policies directly on their websites.